Design and Fabrication of Laccase Enzyme Biosensor Based on Graphene Oxide and Polyaniline for the Measurement of Dephostatin - Mitra Ghodrati Shahtouri; Hamed Fathi; Davod Ilbeigi; Mehdi Mogharabi-Manzari; Ebrahim Fooladi (Journal of Mazandaran University of Medical Sciences)
Background and purpose: A biosensor is composed of two main components: a biological sensing element and a transducer, which together determine the concentration of the analyte by facilitating a biological reaction near the transducer to improve detection capabilities. Compared to traditional analyte measurement and biochemical control methods, biosensors offer advantages such as reusability, fast response times, and high specificity. Laccase is a critical enzyme within the oxidoreductase family, with catalytic properties particularly effective toward ortho- and para-diphenols, depending on the producing organism. Unlike many enzymes that act exclusively on a specific substrate, laccase catalyzes the oxidation of a broad range of substrates, including diphenols, polyphenols, diamines, methoxyphenols, aromatic amines, and ascorbate. Protein tyrosine phosphatases are a class of enzymes that remove phosphate groups from tyrosine residues in proteins. This project aimed to design and develop an enzyme-based biosensor using modified screen-printed carbon electrodes with high sensitivity and selectivity for accurate and rapid dephostatin measurement. Materials and methods: The biosensor was fabricated by immobilizing laccase on the electrode surface. First, the surface of the screen-printed carbon electrode was modified with a graphene oxide/polyaniline nanocomposite, after which the laccase enzyme was immobilized on the modified surface using EDC/NHS linkers. Electrochemical characteristics of the electrodes were assessed using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Optimal parameters, including oxidation potential, pH, temperature, and concentration, were calibrated. At an oxidation potential of 0.45 V relative to the Ag/AgCl electrode, the current response for each sample was measured with the biosensor. Calibration curves were generated, and measurements were obtained by interpolating the amperometric signals from dephostatin solutions. Dephostatin standards were then introduced to the diluted Nescafe sample (phosphate buffer, 0.05 M, pH 6.5) without any pretreatment, and recovery rates were calculated. Results: By immobilizing graphene oxide and laccase on the electrode surface, the modified electrode exhibited increased cathodic and anodic currents compared to the unmodified electrode in K₄Fe(CN)₆/K₃Fe(CN)₆ solution. Due to the presence of graphene nanoparticles on the electrode surface, the electron transfer rate improved, as indicated by a 20 µA increase. The electrode response was linear across a concentration range of 10 to 900 nM, with a detection limit of 6 nM. Conclusion: Since protein tyrosine phosphatases play essential roles in cell signaling pathways and disease development, the use of dephostatin as an inhibitor has gained interest. Therefore, an accurate and rapid method for dephostatin measurement is crucial in the pharmaceutical industry. The prepared biosensor, which incorporates laccase enzyme and graphene nanoparticles stabilized with a chitosan nanocomposite, allows for precise dephostatin measurement. The laccase enzyme immobilized on the electrode surface can specifically oxidize the dephostatin molecule, producing a unique electrode response for this molecule.